PRODUÇÃO DE MUDAS DE IPÊ BRANCO (TABEBUIA RÓSEO-ALBA) EM DIFERENTES COMPOSIÇÕES DE SUBSTRATOS - ESPINDOLA, Gabriella Almeida dos Santos; ESPINDOLA, Andressa Pereira; RODRIGUES, Pedro Henrique Dias; VIEIRA, Jéssica Dionizio; NUNES, Igor Barros; REGO, Norton Hayd (ANAIS DO ENIC, 2025)
.